Etichette e routine artistica - Giulia Alberti (Aisthesis, 2012)
This paper aims to introduce and analyze the concept of “artistic routine”. This notion is derived from the formula “cognitive routine”, which has a wider range of application and is related to the cognitive sciences. It defines the interaction that takes place between the art perceiver and the perceived artwork, i.e. a distinctive cognitive routine, triggered only by specific identifying marks which are usually associated with artworks.